Exploring the drivers of tracking error constrained portfolio performance - Wade Gunning; Gary Van Vuuren (Cogent Economics & Finance, 2019)
Maximising returns is often the primary goal of asset management but managing and mitigating portfolio risk also plays a significant role. Successful active investing requires outperformance of a benchmark through skillful stock selection and market timing, but these bets necessarily give rise to risk. The risk, relative to the benchmark, is the tracking error and active managers are constrained by investment mandates including a restriction on tracking error. The locus of possible portfolio risks and returns, constrained by a tracking error is elliptical, and the main axis slope's sign and magnitude varies under different market conditions. How these variations affect portfolio performance is explored for the first time. We find that changes in main axis slope (magnitude and sign) acts as an early indicator of portfolio performance and could therefore be used as another risk management tool.
Keywords: C51; D81; G11; G23; 330; maximum diversification; tracking error frontier; main axis slope; portfolio optimisation